Virus Resistant Transgenic Sweet Potato with the CP Gene : Current Challenge and Perspective of its Use - Nishiguchi, Masamichi; Mori, Masaki (Phytoprotection, 1998)
Virus diseases of sweet potato are very prevalent and often seriously damage to the plants. Especially sweet potato feathery mottle virus severe strain (SPFMV-S) causes russet crack disease in Japan. In order to confer virus resistance against SPFMV using current biotechnology, we have produced transgenic sweet potato with an expression vector plasmid harboring the coat protein (CP) gene as well as hygromycin phosphotransferase gene (HPT). The plasmid was introduced into mesophyll protoplasts of a sweet potato breeding line, Chikei 682-11 (Ipomoea batatas L.(Lam.)) by electroporation. Protoplatsts were further cultured in the presence of hygromycin. Some of the hygromycin resistant calli were grown to form adventitious shoots. Southern blot analysis with CP and HPT genes showed that these genes were integrated into the chromosomes in four lines. Expression of the CP gene was confirmed by Northern and dot immuno blot analyses. Each line was grafted with the SPFMV-S infected morning glory (I. nill) to reveal any virus resistance conferred. After three months from the graft-inoculation, these transgenic plants were used for ELISA test in order to know any virus infection. There was no significant differences of ELISA values between the inoculated-transgenic and the non inoculated-virus free plants, suggesting that these transgenic plants were not infected with the virus. They produced storage roots, from which the young shoots were again found to be virus-free by ELISA. We concluded that these transgenic plants were highly resistant to the virus. Concerns about the releasing transgenic plants that contain genes from other species include the potential weediness of the plants as well as the potential flow of the transgenic genes to other plants through normal outcrossing. Usually sweet potato is a vegetatively propagated and hardly flowers during growing seasons in Japan. Under these circumstances it might be safe to release these transgenic plants. One concern unique to virus resistant transgenic plants is that a viral sequence from transgene may be potentially incorporated by RNA recombination into a virus that may infect the transgenic plants. There is no useful information available on the occurrence of recombinant virus under the very high level of resistance. From the point; whether or not the frequency of recombination in the transgenic plants greater than that in plants with two or more viruses, it would be at least much lower in these highly virus resistant transgenic plants.